Enzyme-mediated hyaluronic acid–tyramine hydrogels for the propagation of human embryonic stem cells in 3D. (15th September 2015) - Xu, Keming; Narayanan, Karthikeyan; Lee, Fan; Bae, Ki Hyun; Gao, Shujun; Kurisawa, Motoichi
Graphical abstract: Abstract: The propagation of human embryonic stem cells (hESCs) in three-dimensional (3D) scaffolds facilitates the cell expansion process and supplies pluripotent cells of high quality for broad-spectrum applications in regenerative medicine. Herein, we report an enzyme-mediated hyaluronic acid–tyramine (HA–Tyr) hydrogel that encapsulated and propagated hESCs in 3D. HA–Tyr hydrogels were formed by crosslinking the tyramine moieties with horseradish peroxidase (HRP) and hydrogen peroxide (H2 O2 ). By changing the HRP and H2 O2 concentration, we prepared HA–Tyr hydrogels of different mechanical strength and studied the self-renewal properties of hESCs in these scaffolds. We observed that both the chemical composition and mechanical strength of substrates were important factors affecting cell proliferation and pluripotency. The HA–Tyr hydrogel with a compressive modulus of ∼350 Pa supported the proliferation of hESCs at the pluripotent state in both mTeSR1 medium and mouse embryonic fibroblast (MEF)-conditioned medium. Immunohistochemical analyses revealed that hESCs proliferated well and formed spheroid structures in 3D, without undergoing apoptosis. The hESCs cultured in HA–Tyr hydrogels showed high expression of CD44 and pluripotency markers. These cells exhibited the capability to form cell derivatives of all three embryonic germ layers in vitro and in vivo . In addition, the genetic integrity of the hESCs was unaffected in the 3D cultivation system. Statement of Significance: The scope of this study is to provide a stable 3D cultivation system for the expansion of human embryonic stem cells (hESCs) towards clinical applications. We report an enzyme mediated hyaluronic acid–tyramine (HA–Tyr) hydrogel that encapsulated and propagated hESCs in 3D. Unlike other HA-based photo-crosslinked hydrogel systems reported, we investigated the effects of mechanical strength of hydrogels on the self-renewal properties of hESCs in 3D. Then, we characterized hESCs cultured in hydrogels with lower mechanical strength that best supported the self-renewal of hESCs. Hence, we demonstrated a reliable approach for the controlled propagation of hESCs in 3D. We believe that such an approach would facilitate the development of stem cell-based therapy towards clinical applications.